Pengembangan video animasi teknik dasar sepak bola kelas v sekolah dasr negeri 015 gunung kesiangan - Adila, Fakie; Parlim, Indra Prayoga; Ramadi, Ramadi; Taqwa, Taqwa; Syarihadi, Syarihadi (Jurnal Porkes, 2024)
This research aims to produce an animated video product of basic soccer technique material. This type of research is research and development with the Plomp development model. This development model has 3 research phases, namely preliminary research phase, development or prototyping phase, and assessment phase. Then the product validation stage was carried out with 2 experts. The results of this product validation stage, animated video media get an overall average score from both experts of 95.14% with a very valid category. At the product validation stage, a practicality test was then carried out with teachers and students to determine the level of practicality of the animated video products developed. As for the assessment results at the practicality test stage with the teacher, the animated video product received an average score of 95.2% with a very practical category. While the results of the practicality test assessment of students, animated video products get an average score of 92.46% with a very practical category. The conclusion that the animated video product developed has met the criteria of validity and practicality. Thus, this animated video product of basic soccer technique material can already be used as media in learning basic soccer techniques for students.